Effectiveness of Desmanthus virgatus Leaf Ethyl Acetate Extract and Antiviral Drugs as Antirabies Based on In Silico Study - Hendrawan, Syahrul; Ambarwati, Cindy; Tukiran, Tukiran (Jurnal Pijar Mipa, 2025)
Rabies is a deadly viral disease that has no effective therapy after clinical symptoms appear. This study aims to evaluate the antirabies potential of the dominant compounds in the ethyl acetate extract of Desmanthus virgatus leaves, as well as several antiviral drugs, through an in silico approach. The extract was obtained through maceration and partitioning methods using ethyl acetate solvent, then analyzed using LC-MS, which identified 182 secondary metabolite compounds, and ten dominant compounds were selected for further analysis. These compounds, along with seven antiviral drugs, were docked against the rabies virus glycoprotein (PDB ID: 6LGX) using AutoDockTools 4.2.6 software. The docking results were analyzed based on the values of binding affinity, inhibition constant (Ki), and interaction with active amino acid residues.  Quercitrin and quercimeritrin were the dominant flavonoid glycosides in the ethyl acetate extract of D. virgatus leaves that showed binding affinity values of -8.45 kcal/mol and -8.10 kcal/mol, respectively. In addition, bictegravir and tegobuvir showed binding affinity values of -9.17 kcal/mol and -9.05 kcal/mol, respectively. Four compounds indicated potential as antirabies drugs. Pharmacokinetic feasibility tests using Lipinski parameters showed that most of the dominant compounds violated one or more parameters, especially the number of hydrogen bond donors/acceptors and molecular weight. However, such violations were also found in some antiviral drugs that have been used, such as remdesivir and darunavir. These results suggest that D. virgatus leaf extracts contain compounds with promising potential antirabies activity and deserve further investigation through in vitro and in vivo tests.